2005
DOI: 10.1007/s10528-005-1508-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase M1, T1, P1 Genotypes and Risk for Development of Colorectal Cancer

Abstract: The glutathione S-transferase (GST) supergene family is an important part of cellular enzyme defense against endogenous and exogenous chemicals, many of which have carcinogenic potential. The present investigation was conducted to detect a possible association between polymorphisms at the GSTM1, GSTT1, and GSTP1 genes and the interaction with cigarette smoking and colorectal cancer incidence. We examined 181 patients with colorectal cancer and 204 controls. DNA was extracted from whole blood, and the GSTM1, GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 27 publications
3
35
0
7
Order By: Relevance
“…This suggests the mutant allele is randomly distributed in cancer and control cases. Our results are in harmony with the findings of many other reports, who found no effect of the genotype for GSTP1 on colorectal cancer susceptibility (Welfare et al, 1999;Loktionov et al, 2001;Seow et al, 2002;Ates et al, 2005;Sun et al, 2005). Furthermore, they found that the frequencies for the Val-105 allele were 0.33 for controls, and 0.31 for cases, which are almost similar to that of the present study 0.29 and 0.27 for controls and cancer cases respectively (Welfare et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This suggests the mutant allele is randomly distributed in cancer and control cases. Our results are in harmony with the findings of many other reports, who found no effect of the genotype for GSTP1 on colorectal cancer susceptibility (Welfare et al, 1999;Loktionov et al, 2001;Seow et al, 2002;Ates et al, 2005;Sun et al, 2005). Furthermore, they found that the frequencies for the Val-105 allele were 0.33 for controls, and 0.31 for cases, which are almost similar to that of the present study 0.29 and 0.27 for controls and cancer cases respectively (Welfare et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…GSTP1 has a polymorphic site at codon 105 (exon 5), where an A to G transition causes an Ile to Val substitution (Ile105Val), resulting in lower enzyme activity to variety of electrophilic molecules (Millar et al, 1999;Hayes et al, 2005;McIlwain et al, 2006). Numerous reports assessed the risk of colorectal cancer development in subjects carrying the variant Val GSTP1 allele; however, the results are controversial (Harries et al, 1997;Welfare et al, 1999;Kiyohara, 2000;Grubben et al, 2001;Loktionov et al, 2001;Seow et al, 2002;Ates et al, 2005;Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping for GSTM1, GSTT1 and GSTP1 polymorphisms by PCR-RFLP assay was done following a modified method of Ateş et al (Ateş et al, 2005). The primer sequences of GSTM1, GSTT1 and GSTP1 polymorphisms were 5'-GAACTCCCTGAAAAGCTAAGC-3' (forward) and 5'-GTTGGGGCTCAAATATACGGTGG-3' (reverse), 5'-TTCCTTACTGGTCCTCACATCTC-3' (forward) and 5'-TCACCGGATCAGGCCAGCA-3' (reverse), and 5'-ACCCCAGGGCTCTATGGGAA-3' (forward) and 5'-TGAGGGCACAAGAAGCCCCT-3' (reverse), respectively.…”
Section: Genotypingmentioning
confidence: 99%